Penafsiran Ayat-Ayat Larangan Pembunuhan Anak (Metode Tafsir Maudhu’i Abdul Hayy Al-Farmawi) - Salsabila, Hanna; Akhdiat (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
This research aims to interpret the verses prohibiting child murder using the interpretation method of Maudhu'i Abdul Hayy Al-Farmawi. This type of research is classified as qualitative and relies on written data. The results of this research show that based on the practice of applying the Maudhu'i al-Farmawi method, eight verses discuss the prohibition of killing children, namely QS. Al-An'am Verses 137, 140, 151, QS. Al-Isra Verse 31, At-Takwir verses 8-9, QS. Al-Mumtahanah verse 12, Az-Zukhruf verse 17, An-Nahl verse 58, which are related to each other. The practice of killing children during the Jahiliyah period was caused by fear of poverty and shame. These verses emphasize the importance of protecting children and prohibiting the killing of children for any reason, as well as emphasizing equality between boys and girls in treatment and sustenance. Negative reactions to the birth of girls in Arab society are also emphasized as unwarranted. This practice is considered to violate religious provisions.